P173 'It's definitely the future': Healthcare practitioners' views and experiences of activity monitors to support people with chronic obstructive pulmonary disease (COPD). (11th November 2022) - Wilde, LJ; Clark, C; Percy, C; Ward, G; Wark, PA; Sewell, L
Abstract : Introduction and Objectives: Activity monitors (i.e. apps and wearables) are becoming increasingly utilised by the general population and people with Chronic Obstructive Pulmonary Disease (COPD). Adapting to COVID-19 involved the remote delivery of COPD treatments, including pulmonary rehabilitation. However, research prior to COVID-19 has reported that few healthcare practitioners used activity monitors within treatment and rarely discussed or reviewed patients' activity data. Barriers to utilising patient activity data have included; time, expertise, and scepticism about the benefits of reviewing data. Understanding how healthcare practitioners can incorporate technology and utilise activity data collected at home could enable more effective remote delivery of interventions, healthcare, and treatment. This qualitative research aimed to explore healthcare practitioners' views and experiences of supporting people with COPD who have used activity monitors. Methods: Seventeen semi-structured telephone or online interviews were conducted with healthcare practitioners between September 2020 and May 2021. Healthcare practitioner occupations included nurse, occupational therapist, physician, and physiotherapist. Participants all had experience of supporting people with COPD who had used activity monitors. Interviews were analysed using inductive thematic analysis. Results: Five preliminary themes were developed underlining healthcare practitioners' experiences of supporting patients with COPD using activity monitors; 1) Using skills and experience to increase accessibility, digital literacy and engagement, 2) The importance of discussion and dialogue to support patients with using activity monitors, 3) Using objectively monitored activity levels to encourage physical activity and support exercise prescription, 4) Implementation of research into usual care and applications to real life, and 5) Benefits of using activity monitors and their future potential. Conclusions: This study highlighted that HCPs recognise the potential for activity monitors to positively impact patients' ability to self-manage their COPD. However, there is also a need for training, best practice guidelines and/or recommendations to support HCPs to engage with activity monitors. If physical activity data collected at home is utilised and integrated effectively and efficiently into healthcare practices to support COPD treatment, there is potential for activity monitors to positively impact patients' health and self-management behaviours.